Search All of the Math Forum:
Views expressed in these public forums are not endorsed by
NCTM or The Math Forum.


ticbol
Posts:
116
Registered:
1/25/05


Re: Please help me simplify this expression.
Posted:
Jan 24, 2005 2:18 AM


Look at this:
[x(x+2)^(1/2) + (x+2)^(1/2) ] / (x+2)^(3/2)
We clear the negative exponent, = [x/(x+2)^(1/2) + (x+2)^(1/2) ] / (x+2)^(3/2)
We simplify those inside the bracket, = [{x +(x+2)^(1/2)* (x+2)^(1/2)} / {(x+2)^(1/2)} ] / (x+2)^(3/2) = [{x +(x+2)^1} / {(x+2)^(1/2)} ] / (x+2)^(3/2) = [{x +x+2} / {(x+2)^(1/2)} ] / (x+2)^(3/2) = [{2x +2} / {(x+2)^(1/2)} ] / (x+2)^(3/2) = [{2(x+1)} / {(x+2)^(1/2)} ] / (x+2)^(3/2)
We carry on, = [{2(x+1)} / {(x+2)^(1/2)} ] * [1/ (x+2)^(3/2)] = [2(x+1)] / [{(x+2)^(1/2)} * {(x+2)^(3/2)}] = [2(x+1)] / [(x+2)^(4/2)] = 2(x+1) / (x+2)^2 answer.
 submissions: post to k12.ed.math or email to k12math@k12groups.org private email to the k12.ed.math moderator: kemmoderator@k12groups.org newsgroup website: http://www.thinkspot.net/k12math/ newsgroup charter: http://www.thinkspot.net/k12math/charter.html



